Past and present research on sheep and goat breeding in Nigeria - Olayiwole, M.B.; Adu, I.F. (1989)
Presents the past and present research findings on sheep and goat breeding in Nigeria. Attempts were made in the past at exploiting their genetic potentials through pure breeding and selection while a number of exotic breeds were used on the indigenous sheep and goats to improve goats and sheep skin quality, meat, wool and milk production. The present breeding programme aims at improving growth rate and prolificacy in sheep and goat through pure breeding and selection of the indigenous breeds for skin, meat and milk. Data on reproduction traits, body weight, growth rate, carcass yield, birth weight, lambing and weaning weights included.